Partial pressure (or fugacity) of carbon dioxide, salinity and other variables collected from Surface underway observations using Carbon dioxide (CO2) gas analyzer, Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement and other instruments from HEALY in the Arctic Ocean, Beaufort Sea and others from 2011-05-27 to 2011-12-16 (NCEI Accession 0144345) ... - Takahashi, Taro; Sweeney, Colm; Sutherland, Stewart C. (NOAA National Centers for Environmental Information, 2016)
This dataset includes Surface underway data collected from HEALY in the Arctic Ocean, Beaufort Sea, Bering Sea, Coastal Waters of SE Alaska, Gulf of Alaska, Hawaiian Islands Humpback Whale National Marine Sanctuary, North Pacific Ocean and Northwest Passage from 2011-05-27 to 2011-12-16. These data include BAROMETRIC PRESSURE, Partial pressure (or fugacity) of carbon dioxide - water, SALINITY and SEA SURFACE TEMPERATURE. The instruments used to collect these data include Carbon dioxide (CO2) gas analyzer and Shower head chamber equilibrator for autonomous carbon dioxide (CO2) measurement. These data were collected by Stewart C. Sutherland and Taro Takahashi of Lamont-Doherty Earth Observatory (LDEO) and Colm Sweeney of NOAA Earth System Research Laboratory (ESRL) as part of the VOS_Healy_Lines_2011 dataset. ...